Annual spatiotemporal migration schedules in three larger insectivorous birds: European nightjar, common swift and common cuckoo. Issue 1 (December 2017) - Jacobsen, Lars; Jensen, Niels; Willemoes, Mikkel; Hansen, Lars; Desholm, Mark; Fox, Anthony; Tøttrup, Anders; Thorup, Kasper
Abstract Background Knowledge of spatiotemporal migration patterns is important for our understanding of migration ecology and ultimately conservation of migratory species. We studied the annual migration schedules of European nightjar, a large nocturnal insectivore and compared it with two other larger migratory insectivores, common swift and common cuckoo. All species breed in North Europe and winter in sub-Saharan Africa, but estimating their spatiotemporal non-breeding distributions from observations is complicated by the occurrence of similar local African species. We used geolocators to track the annual migrations of nightjars and swifts and compared these with satellite tracking of cuckoo migration. Results Individuals of the three species migrated to wintering grounds centered in Central Africa, except some common swifts that remained in West Africa, crossing or circumventing the Sahara along different routes in spring and fall. Overall, all species showed similar regional and seasonal use of several stopover areas during migration. Among the three species, European nightjars and common cuckoos showed the most similar spatiotemporal migration patterns. The nightjars wintered in SW Central Africa and breeding and wintering made up by far the two longest stationary periods. Swifts were generally more mobile, and some individuals progressively visited areas further east in East Africa during winter and further west in West Africa on spring migration; this species also spent less time on stopovers, but more on wintering areas. Cuckoos were intermediate in their extent of movements. The speed of nightjar spring migration was equal to that of fall migration, in contrast to the two other species where spring return to breeding areas was faster. Conclusions Ecological requirements are potentially useful for understanding spatiotemporal migration patterns and causes of declines in migratory species.